2017
DOI: 10.1080/21645515.2017.1397245
|View full text |Cite
|
Sign up to set email alerts
|

Safety of specific immunotherapy using an ultra-rush induction regimen in bee and wasp allergy

Abstract: We found that the ultra-rush protocol (similar to the rush protocol) using the Venomenhal vaccine is safer than the conventional protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Of these, two thirds (n = 10) reached the cumulative dose of 101.1 μg in a further UR, 15 days later, with a premedication reinforcement and using the same UR protocol. In contrast to other studies published to date (16,17,21,22) our study has much more patients submitted honey bee VIT, and also 13 patients that underwent an UR protocol with paper wasp venom. These are particular aspects related to the environmental exposure to insects' stings in our country.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Of these, two thirds (n = 10) reached the cumulative dose of 101.1 μg in a further UR, 15 days later, with a premedication reinforcement and using the same UR protocol. In contrast to other studies published to date (16,17,21,22) our study has much more patients submitted honey bee VIT, and also 13 patients that underwent an UR protocol with paper wasp venom. These are particular aspects related to the environmental exposure to insects' stings in our country.…”
Section: Discussionmentioning
confidence: 86%
“…In these protocols the protective dose of 100 μg venom is reached in a quicker way, decreasing the potential risk of an anaphylactic sting reaction (1,8,14). Over the years, several studies have shown that this induction protocol is safe and effective (15,16,17,18). Nevertheless, there are still some concerns related to the occurrence of severe systemic reactions during the UR protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Existing study data investigating whether certain treatment schedules are associated with a higher frequency of SR are highly conflicting [11,13,14,[22][23][24]. Large-scale studies ascribed accelerated protocols to a higher incidence of SR [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is well recognized that allergic reactions are a common adverse effect of rush DS. For example, a recent study evaluating desensitization regimens for bee and wasp venom reported that allergic reactions occurred in 13.7% of patients on an ultra‐rush regimen, 14.3% of patients on a rush regimen, and 26.5% of patients on a conventional immunotherapy regimen . This suggests that mast cell and basophil activation likely occur to some level in many patients undergoing desensitization.…”
Section: Discussionmentioning
confidence: 99%